Question
upstudy study bank question image url

Consider the quadratic number pattern: \( 2 ; 3 ; 6 ; 11 ; \ldots \) \( \begin{array}{ll}\text { (1) Determine the } 5 \text { th term. } & \text { (2) Determine the general } \\ \text { (3) Determine the } 50 \text { th term. } & \text { (4) Which term is equal to } \\ \text { Given the quadratic number pattern: } 3 ; 3 ; 4 ; 6 ; \ldots \text { Determine } \\ \text { (1) a formula for the } n \text {-th tern. } & \text { (2) } T_{\text {tix }}\end{array} \)

Ask by Lambert Haynes. in South Africa
Jan 15,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The 5th term is 18, the general formula for the nth term is \( T_n = n^2 - 2n + 3 \), and the 50th term is 2403.

Solution

To determine the 5th term in the quadratic number pattern \(2; 3; 6; 11; \ldots\), we need to find the general formula for the nth term. Given the quadratic number pattern \(2; 3; 6; 11; \ldots\), we can observe that the differences between consecutive terms are increasing by 1 each time. This indicates that the pattern follows a quadratic relationship. Let's denote the nth term as \(T_n\). We can start by finding the differences between consecutive terms: - \(T_2 - T_1 = 3 - 2 = 1\) - \(T_3 - T_2 = 6 - 3 = 3\) - \(T_4 - T_3 = 11 - 6 = 5\) From the differences, we can see that the pattern of differences is increasing by 2 each time. This suggests that the quadratic relationship can be represented as \(T_n = an^2 + bn + c\), where \(a\), \(b\), and \(c\) are constants to be determined. Using the given terms, we can set up a system of equations to solve for \(a\), \(b\), and \(c\): 1. \(T_1 = 2 = a(1)^2 + b(1) + c\) 2. \(T_2 = 3 = a(2)^2 + b(2) + c\) 3. \(T_3 = 6 = a(3)^2 + b(3) + c\) Solving this system of equations will give us the values of \(a\), \(b\), and \(c\), which we can then use to find the general formula for the nth term. Let's proceed with solving the system of equations to find the values of \(a\), \(b\), and \(c. Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}2=a+b+c\\3=4a+2b+c\\6=9a+3b+c\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}a=2-b-c\\3=4a+2b+c\\6=9a+3b+c\end{array}\right.\) - step2: Substitute the value of \(a:\) \(\left\{ \begin{array}{l}3=4\left(2-b-c\right)+2b+c\\6=9\left(2-b-c\right)+3b+c\end{array}\right.\) - step3: Simplify: \(\left\{ \begin{array}{l}3=8-2b-3c\\6=18-6b-8c\end{array}\right.\) - step4: Solve the equation: \(\left\{ \begin{array}{l}b=\frac{5-3c}{2}\\6=18-6b-8c\end{array}\right.\) - step5: Substitute the value of \(b:\) \(6=18-6\times \frac{5-3c}{2}-8c\) - step6: Simplify: \(6=3+c\) - step7: Swap the sides: \(3+c=6\) - step8: Move the constant to the right side: \(c=6-3\) - step9: Subtract the numbers: \(c=3\) - step10: Substitute the value of \(c:\) \(b=\frac{5-3\times 3}{2}\) - step11: Simplify: \(b=-2\) - step12: Substitute the values of \(b,c:\) \(a=2-\left(-2\right)-3\) - step13: Simplify: \(a=1\) - step14: Calculate: \(\left\{ \begin{array}{l}a=1\\b=-2\\c=3\end{array}\right.\) - step15: Check the solution: \(\left\{ \begin{array}{l}a=1\\b=-2\\c=3\end{array}\right.\) - step16: Rewrite: \(\left(a,b,c\right) = \left(1,-2,3\right)\) The solution to the system of equations is \(a = 1\), \(b = -2\), and \(c = 3\). Therefore, the general formula for the nth term in the quadratic number pattern is \(T_n = n^2 - 2n + 3\). Now, we can use this formula to find the 5th term: \(T_5 = 5^2 - 2(5) + 3 = 25 - 10 + 3 = 18\). So, the 5th term in the quadratic number pattern is 18. Next, we need to determine the 50th term using the same formula: \(T_{50} = 50^2 - 2(50) + 3 = 2500 - 100 + 3 = 2403\). Therefore, the 50th term in the quadratic number pattern is 2403. Finally, we need to find the term that is equal to 2403 using the same formula: \(2403 = n^2 - 2n + 3\). Solving for \(n\), we get: \(n^2 - 2n + 3 = 2403\) \(n^2 - 2n - 2400 = 0\) Solving this quadratic equation, we find that \(n = 50\). Therefore, the term that is equal to 2403 is the 50th term in the quadratic number pattern.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

To find the 5th term of the pattern \(2, 3, 6, 11, \ldots\), we first look at the differences between terms: \(3-2=1\), \(6-3=3\), and \(11-6=5\). The next differences would be \(2\) (i.e., \(3-1\), \(5-3\)), suggesting a pattern in second differences. Continuing this, the 5th term can be calculated as \(11 + (5+2) = 11 + 7 = 18\). For the pattern \(3, 3, 4, 6, \ldots\), the first step is to find the differences: \(3-3=0\), \(4-3=1\), \(6-4=2\). The second differences \(1-0=1\) and \(2-1=1\) suggest the underlying quadratic pattern. Thus, we can express the \(n\)-th term as \(T_n = an^2 + bn + c\). Plugging in the values for the first three terms, we can determine that \(T_n = \frac{1}{2}n^2 + 2\), which fits well, providing a distinct formula.

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy